CONDUTA DO CIRURGIÃO-DENTISTA NA EXODONTIA DE DENTES INCLUSOS OU IMPACTADOS (REMUNOM, 2024)
This article explores the conduct of dentists in the exodontia of impacted teeth, addressing everything from the definition of impacted teeth (those that do not erupt into the oral cavity in normal time), etiology (associated with various factors such as lack of space, presence of another tooth, dense bone or genetic abnormalities) to diagnosis (made with the aid of clinical and radiographic examination, including panoramic, periapical and computed tomography radiography) and treatment (by means of exodontia, the most common treatment, orthodontics or tooth transplantation). In this sense, the objectives are: to analyze the clinical, radiographic and therapeutic aspects of impacted teeth, to propose a comprehensive guide for the diagnosis, treatment and follow-up of the condition and, finally, to support the work of dentists in exodontia. Methodologically, an integrative review of the literature was carried out, of a qualitative type, selecting articles since 2019 from databases such as Google Scholar, Virtual Health Library and Brazilian Journal of Development, among others. The search focused on terms such as "impacted teeth", "etiology", "complications", "diagnosis", "treatment" and "dentist's conduct". The study provides scientific support for the proper performance of dentists in the exodontia of impacted teeth, contributing to accurate diagnosis, choice of ideal treatment and prevention of complications.